2005
DOI: 10.1097/01.pas.0000163359.32734.f9
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Stromal Tumors of Neurofibromatosis Type I (von Recklinghausen's Disease)

Abstract: Gastrointestinal stromal tumor (GIST), as well as the hyperplastic lesions of intestinal neural tissue and its supporting structures, is a gastrointestinal complication of type 1 neurofibromatosis (NF1) (von Recklinghausen's disease). In the present study, we analyzed the histologic and immunohistochemical features, and the c-kit and PDGFRA gene mutations of 36 GISTs derived from 9 NF1 patients. Distinctively, multiple GISTs arose preferentially in the small intestine. The histologic features of NF1-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0
12

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(130 citation statements)
references
References 29 publications
2
116
0
12
Order By: Relevance
“…14 Rectal GIST, although rare, most commonly present with haematochezia. 15 GIST may occur as part of a syndrome, such as Carney's triad (gastric GIST, paraganglioma, pulmonary chondroma), 16 Neurofibromatosis type 1 (with predominately spindle cell type of GIST) 17,18 or Von Hippel Lindau disease.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…14 Rectal GIST, although rare, most commonly present with haematochezia. 15 GIST may occur as part of a syndrome, such as Carney's triad (gastric GIST, paraganglioma, pulmonary chondroma), 16 Neurofibromatosis type 1 (with predominately spindle cell type of GIST) 17,18 or Von Hippel Lindau disease.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…However, one study identified two KIT (Pro627Leu and Ile653Thr) and two PDGFRA (Pro589Lys and Arg822Ser) missense mutations in two separate lesions from two patients. 120 These mutations might be random genetic events related to the tumor progression. In another study, an identical 1697TϾA mutation leading at the protein level to Val559Asp substitution has been identified in three tumors from one patient.…”
Section: Pdgfra Enzymatic Domain Mutation (Exon 14 Exon 18)mentioning
confidence: 99%
“…16,43,117 KIT and PDGFRA mutational status in NF1 and pediatric and Carney triad GISTs Several studies evaluated KIT and PDGFRA mutation status in GISTs from neurofibromatosis type 1 (NF1) patients. [118][119][120][121][122][123][124] In general, no mutations in GIST-specific KIT or PDGFRA mutational "hot spots" have been found in multiple tumors from NF1 patients. However, one study identified two KIT (Pro627Leu and Ile653Thr) and two PDGFRA (Pro589Lys and Arg822Ser) missense mutations in two separate lesions from two patients.…”
Section: Pdgfra Enzymatic Domain Mutation (Exon 14 Exon 18)mentioning
confidence: 99%
“…In re cent ye ars, examp les of fa mi li al GIST ha ve be en re por ted in which germ li ne mu ta ti ons of KIT or PDGFRA re sult in mul tip le GISTs, skin di sor ders, and ot her ab nor ma li ti es. Alt ho ugh most of mul tip le GISTs pa ti ents in the li te ra tu re de ve lo ped in the set ting of NF1, 4,5,12 mul tip li city in spo ra dic GIST pa ti ents wit ho ut fa mily his tory or NF-1 has be en al so des cri bed. 4 In the pre sent study, we analy zed the his to lo gi cal and im mu nohis toc he mi cal fe a tu res from three NF1 and one spo ra dic pa ti ent.…”
Section: Discussionmentioning
confidence: 99%